International study of seventh grade students’ understandings of scientific inquiry: the cases of Israel and South Africa - Mamlok‐Naaman, Rachel; Blonder, Ron; Gaigher, Estelle; Hattingh, Annemarie; Kay, Gillian (Enseñanza de las ciencias: revista de investigación y experiencias didácticas, 2017)
Although understanding of scientific inquiry (SI) is included in science education reform documents around the world, virtually nothing is known about middle school students’ understandings of scientific inquiry. This is partially due to the lack of any valid assessment tool. However, a valid and reliable assessment has recently been developed and published. The Views About Scientific Inquiry [VASI]) (Lederman et. al. , 2014). The purpose of this international project was to acquire the first baseline data on what middle school students know. In many countries, science is not formally taught until middle school, which is the rationale for choosing seventh grade students for this investigation.
Keywords: openalex:import

African Climate Change: Taking the Shorter Route - Washington, Richard; Harrison, Mike T.; Conway, Declan; Black, Emily; Challinor, Andrew J.; Grimes, D. I. F.; Jones, R. G.; Morse, Andrew P.; Kay, Gillian; Todd, Martin C. (Bulletin of the American Meteorological Society, 2006)
Numerous factors are associated with poverty and underdevelopment in Africa, including climate variability. Rainfall, and climate more generally, are implicated directly in the United Nations “Millennium Development Goals” to eradicate extreme poverty and hunger, and reduce child mortality and incidence of diseases such as malaria by the target date of 2015. But, Africa is not currently on target to meet these goals. We pose a number of questions from a climate science perspective aimed at understanding this background: Is there a common origin to factors that currently constrain climate science? Why is it that in a continent where human activity is so closely linked to interannual rainfall variability has climate science received little of the benefit that saw commercialization driving meteorology in the developed world? What might be suggested as an effective way for the continent to approach future climate variability and change? We make the case that a route to addressing the challenges of climate change in Africa rests with the improved management of climate variability. We start by discussing the constraints on climate science and how they might be overcome. We explain why the optimal management of activities directly influenced by interannual climate variability (which include the development of scientific capacity) has the potential to serve as a forerunner to engagement in the wider issue of climate change. We show this both from the perspective of the climate system and the institutions that engage with climate issues. We end with a thought experiment that tests the benefits of linking climate variability and climate change in the setting of smallholder farmers in Limpopo Province, South Africa.
Keywords: openalex:import

African Climate Change: Taking the Shorter Route - Washington, Richard; Harrison, Mike T.; Conway, Declan; Black, Emily; Challinor, Andrew J.; Grimes, D. I. F.; Jones, R. G.; Morse, Andrew P.; Kay, Gillian; Todd, Martin C. (Bulletin of the American Meteorological Society, 2006)
Numerous factors are associated with poverty and underdevelopment in Africa, including climate variability. Rainfall, and climate more generally, are implicated directly in the United Nations “Millennium Development Goals” to eradicate extreme poverty and hunger, and reduce child mortality and incidence of diseases such as malaria by the target date of 2015. But, Africa is not currently on target to meet these goals. We pose a number of questions from a climate science perspective aimed at understanding this background: Is there a common origin to factors that currently constrain climate science? Why is it that in a continent where human activity is so closely linked to interannual rainfall variability has climate science received little of the benefit that saw commercialization driving meteorology in the developed world? What might be suggested as an effective way for the continent to approach future climate variability and change? We make the case that a route to addressing the challenges of climate change in Africa rests with the improved management of climate variability. We start by discussing the constraints on climate science and how they might be overcome. We explain why the optimal management of activities directly influenced by interannual climate variability (which include the development of scientific capacity) has the potential to serve as a forerunner to engagement in the wider issue of climate change. We show this both from the perspective of the climate system and the institutions that engage with climate issues. We end with a thought experiment that tests the benefits of linking climate variability and climate change in the setting of smallholder farmers in Limpopo Province, South Africa.
Keywords: openalex:import

African Climate Change: Taking the Shorter Route - Washington, Richard; Harrison, Mike T.; Conway, Declan; Black, Emily; Challinor, Andrew J.; Grimes, D. I. F.; Jones, R. G.; Morse, Andrew P.; Kay, Gillian; Todd, Martin C. (Bulletin of the American Meteorological Society, 2006)
Numerous factors are associated with poverty and underdevelopment in Africa, including climate variability. Rainfall, and climate more generally, are implicated directly in the United Nations “Millennium Development Goals” to eradicate extreme poverty and hunger, and reduce child mortality and incidence of diseases such as malaria by the target date of 2015. But, Africa is not currently on target to meet these goals. We pose a number of questions from a climate science perspective aimed at understanding this background: Is there a common origin to factors that currently constrain climate science? Why is it that in a continent where human activity is so closely linked to interannual rainfall variability has climate science received little of the benefit that saw commercialization driving meteorology in the developed world? What might be suggested as an effective way for the continent to approach future climate variability and change? We make the case that a route to addressing the challenges of climate change in Africa rests with the improved management of climate variability. We start by discussing the constraints on climate science and how they might be overcome. We explain why the optimal management of activities directly influenced by interannual climate variability (which include the development of scientific capacity) has the potential to serve as a forerunner to engagement in the wider issue of climate change. We show this both from the perspective of the climate system and the institutions that engage with climate issues. We end with a thought experiment that tests the benefits of linking climate variability and climate change in the setting of smallholder farmers in Limpopo Province, South Africa.
Keywords: openalex:import

African Climate Change: Taking the Shorter Route - Washington, Richard; Harrison, Mike T.; Conway, Declan; Black, Emily; Challinor, Andrew J.; Grimes, D. I. F.; Jones, R. G.; Morse, Andrew P.; Kay, Gillian; Todd, Martin C. (Bulletin of the American Meteorological Society, 2006)
Numerous factors are associated with poverty and underdevelopment in Africa, including climate variability. Rainfall, and climate more generally, are implicated directly in the United Nations “Millennium Development Goals” to eradicate extreme poverty and hunger, and reduce child mortality and incidence of diseases such as malaria by the target date of 2015. But, Africa is not currently on target to meet these goals. We pose a number of questions from a climate science perspective aimed at understanding this background: Is there a common origin to factors that currently constrain climate science? Why is it that in a continent where human activity is so closely linked to interannual rainfall variability has climate science received little of the benefit that saw commercialization driving meteorology in the developed world? What might be suggested as an effective way for the continent to approach future climate variability and change? We make the case that a route to addressing the challenges of climate change in Africa rests with the improved management of climate variability. We start by discussing the constraints on climate science and how they might be overcome. We explain why the optimal management of activities directly influenced by interannual climate variability (which include the development of scientific capacity) has the potential to serve as a forerunner to engagement in the wider issue of climate change. We show this both from the perspective of the climate system and the institutions that engage with climate issues. We end with a thought experiment that tests the benefits of linking climate variability and climate change in the setting of smallholder farmers in Limpopo Province, South Africa.
Keywords: openalex:import

African Climate Change: Taking the Shorter Route - Washington, Richard; Harrison, Mike T.; Conway, Declan; Black, Emily; Challinor, Andrew J.; Grimes, D. I. F.; Jones, R. G.; Morse, Andrew P.; Kay, Gillian; Todd, Martin C. (Bulletin of the American Meteorological Society, 2006)
Numerous factors are associated with poverty and underdevelopment in Africa, including climate variability. Rainfall, and climate more generally, are implicated directly in the United Nations “Millennium Development Goals” to eradicate extreme poverty and hunger, and reduce child mortality and incidence of diseases such as malaria by the target date of 2015. But, Africa is not currently on target to meet these goals. We pose a number of questions from a climate science perspective aimed at understanding this background: Is there a common origin to factors that currently constrain climate science? Why is it that in a continent where human activity is so closely linked to interannual rainfall variability has climate science received little of the benefit that saw commercialization driving meteorology in the developed world? What might be suggested as an effective way for the continent to approach future climate variability and change? We make the case that a route to addressing the challenges of climate change in Africa rests with the improved management of climate variability. We start by discussing the constraints on climate science and how they might be overcome. We explain why the optimal management of activities directly influenced by interannual climate variability (which include the development of scientific capacity) has the potential to serve as a forerunner to engagement in the wider issue of climate change. We show this both from the perspective of the climate system and the institutions that engage with climate issues. We end with a thought experiment that tests the benefits of linking climate variability and climate change in the setting of smallholder farmers in Limpopo Province, South Africa.
Keywords: openalex:import